2020
DOI: 10.1096/fj.201903236r
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neurons directly promote angiogenesis in response to inflammation via substance P signaling

Abstract: Blood vessels and nerves travel together to supply most tissues in the body. However, there is a knowledge gap in the mechanisms underlying the direct regulation of angiogenesis by nerves. In the current study, we examined the regulation of angiogenesis by sensory nerves in response to inflammation using the cornea, a normally avascular and densely innervated ocular tissue, as a model. We used desiccating stress as an inflammatory stimulus in vivo and found that sub‐basal and epithelial nerve densities in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Recently, several preclinical studies have reported using a dry eye animal model to elucidate the roles of neuropeptide/neuropeptide-specific receptors in the pathogenesis of DED ( Table 3 ). There have been reports that the expression of SP is elevated in the cornea, conjunctiva, and trigeminal ganglion by exposure to DS in the controlled-environment chamber (CEC) [ 218 , 219 , 220 ]. Yu et al [ 218 ] investigated the expression of SP at the ocular surface and evaluated its effect on the maturation of APCs, the key cells involved in the induction of the Th17-mediated response in DED.…”
Section: Recent Results Showing the Roles Of Neuropeptides In The Pathogenesis Of Dry Eye Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several preclinical studies have reported using a dry eye animal model to elucidate the roles of neuropeptide/neuropeptide-specific receptors in the pathogenesis of DED ( Table 3 ). There have been reports that the expression of SP is elevated in the cornea, conjunctiva, and trigeminal ganglion by exposure to DS in the controlled-environment chamber (CEC) [ 218 , 219 , 220 ]. Yu et al [ 218 ] investigated the expression of SP at the ocular surface and evaluated its effect on the maturation of APCs, the key cells involved in the induction of the Th17-mediated response in DED.…”
Section: Recent Results Showing the Roles Of Neuropeptides In The Pathogenesis Of Dry Eye Diseasementioning
confidence: 99%
“…Taketani et al [ 220 ] showed that a significant increase in SP levels promotes Treg dysfunction in DED, and blockade of SP effectively restores Treg function and alleviates DED severity. Additionally, Liu et al [ 219 ] investigated the regulation of angiogenesis by sensory nerves in response to DS using a coculture system of vascular endothelial cells and trigeminal ganglion sensory neurons harvested from DED mice. SP potently promoted the activation of the vascular endothelial cells in vitro, and blockade of SP signaling with spantide I, an antagonist of NK1R, significantly reduced corneal neovascularization in vivo, suggesting that sensory neurons directly promote angiogenesis via SP signaling in response to inflammation in the cornea.…”
Section: Recent Results Showing the Roles Of Neuropeptides In The Pathogenesis Of Dry Eye Diseasementioning
confidence: 99%
See 1 more Smart Citation
“… 10 More recently, it has been reported that sensory neurons directly promote angiogenesis via SP signaling in response to corneal inflammation. 41 …”
Section: Discussionmentioning
confidence: 99%
“… 89 Sensory nerves that travel alongside blood vessels promote angiogenesis via substance P mediated signaling during inflammation. 89 , 90 A similar neuronal‐mediated process promoting angiogenesis appears to function in the TME. Adrenergic nerves in the TME release norepinephrine triggering an angiogenic switch by signaling through the ADRB2 on endothelial cells, thereby promoting increased vascularization of the TME.…”
Section: Function Of Nerves In Cancer Cell Behavior and The Tumor Microenvironmentmentioning
confidence: 99%